The motivation of e-commerce entrepreneurs in rural China - Tai, Zhang (2020)
This research seeks to detect the entrepreneurial motivation of e-commerce entrepreneurs in rural China and explore whether and how e-commerce can enable these entrepreneurs achieve their motivation. This research employed method from the qualitative methodology, interviewing 5 respondents based on semi-structure interview method. It is concluded in my research that the motivations of e-commerce entrepreneurs in rural China can be classified as wealth generation, achieving autonomy, and contributing to their community. Based on these motivations, this research also discussed the how e-commerce helped them achieve (or not) their motivation. This dissertation has an implication for understanding the e-commerce entrepreneurship from their individual perspective.